Representation of Liberal Feminism on the 2020 Mulan Movie - Indriani, Tri; Wenerda, Indah (Universitas Ahmad Dahlan, 2024)
This research aims to explore the characteristics of Mulan as the only female soldier of the Chinese emperor in challenging the stereotypes of women that have been formed in society. The film shows Mulan's adventures as the only female soldier of the Chinese emperor. This research method uses a qualitative descriptive approach through observation and analysis of each scene and narrative available to explore the feminist values contained in this film. There were findings that Hua Mulan made efforts to challenge the stereotypes that developed regarding women. Hua Mulan challenges the boundaries that society places on women. In conclusion, Hua Mulan shows the characteristics of liberal feminism in the character Mulan which focuses on individual rights in obtaining opportunities, changes in social and legal policies that are no different for women.